The Influence Of Marketing Mix And Online Reviews On Purchasing Decisions Through Shopee E-Commerce In Medan Perjuangan Subdistrict - Edward Alezandro Lbn. Raja; Maria Ayustina Doke Ria; Togu Harlen Lbn. Raja; Karina Silaen; Adiwima Zebua (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The research findings indicated that the t-test results for the marketing mix variables showed a calculated t-value of 6,378 > the tabulated t-value of 1,984. This indicates that the marketing mix significantly influences purchasing decisions on the shopee e-commerce platform in the Medan Perjuangan Subdistrict. On the other hand, the t-test results for the online review variabel showed a calculated t-value of -3,384 < 1,984, suggesting that online reviews have an influence on purchasing decisions in shopee e-commerce, but the influence is not statistically significant in the Medan Perjuangan Subdistrict. Furthermore, the combined effect of marketing mix and online reviews, as indicated by the F-test (calculated F-value of 20,488 > tabulate F-value of 3.09), signifies a significant joint influence on purchasing decisions. The coefficient of determination (R2) test resulted in a value of 41.2%, indicating the proportion of variance explained by the model.